Immune cells in the epithelial immune microenvironment of psoriasis: emerging therapeutic targets - Li, Lisha; Lu, Jiaye; Liu, Jun; Wu, Junchao; Zhang, Xinyue; Meng, Yu; Wu, Xiying; Tai, Zongguang; Zhu, Quangang; Chen, Zhongjian (Frontiers in Immunology, 2024)
Psoriasis is a chronic autoimmune inflammatory disease characterized by erroneous metabolism of keratinocytes. The development of psoriasis is closely related to abnormal activation and disorders of the immune system. Dysregulated skin protective mechanisms can activate inflammatory pathways within the epithelial immune microenvironment (EIME), leading to the development of autoimmunerelated and inflammatory skin diseases. In this review, we initially emphasized the pathogenesis of psoriasis, paying particular attention to the interactions between the abnormal activation of immune cells and the production of cytokines in psoriasis. Subsequently, we delved into the significance of the interactions between EIME and immune cells in the emergence of psoriasis. A thorough understanding of these immune processes is crucial to the development of targeted therapies for psoriasis. Finally, we discussed the potential novel targeted therapies aimed at modulating the EIME in psoriasis. This comprehensive examination sheds light on the intricate underlying immune mechanisms and provides insights into potential therapeutic avenues of immune-mediated inflammatory diseases.